Effects of nonsteroidal anti‐inflammatory drug (NSAID) use upon male gonadal function: A national, population‐based study. (18th February 2020) - Halpern, Joshua A.; Fantus, Richard J.; Chang, Cecilia; Keeter, Mary Kate; Helfand, Brian; Bennett, Nelson E.; Brannigan, Robert E.
Abstract: Recent data have suggested that short‐term NSAID use induces a state of compensated hypogonadism. Our aim was to investigate the association between chronic, regular NSAID use and compensated hypogonadism in a large, nationally representative cohort, the US National Health and Nutrition Examination Survey (NHANES) database. Men 20–80 years who answered the analgesic use questionnaire and underwent hormonal testing were included. Multivariable regression was utilised to determine the relationship between NSAID use and serum testosterone (T), anti‐Mullerian hormone (AMH) and T:AMH ratio. Among 3, 749 men, 505 (13.5%) reported regular NSAID use and 3, 244 (86.5%) did not. Regular users had lower T (440.7 ± 27.0 vs. 557.0 ± 24.9 ng/dl, p  = .005) and albumin (43.8 ± 0.2 vs. 45.1 ± 0.1, p  < .001) compared to nonregular users. On multivariable analysis, only active smoking was significantly associated with T, AMH and T:AMH ratio ( p  < .001, p  = .036 and p  = .005 respectively). Regular NSAID use was not associated with T, AMH or T:AMH ratio ( p  = .523, p  = .974, and p  = .872 respectively). In this nationally representative sample of US men, regular and chronic NSAID use was not associated with alterations in T or compensated hypogonadism. These data should reassure patients and clinicians regarding the safety of NSAID use with respect to the risk of alteration in the hypothalamic–pituitary–gonadal axis.